Study on cocrystal formation between ibuprofen and glutaric acid via slow evaporation technique: article - Rahamat, Farah Alia; Othman, Muhamad Fitri (2017)
Ibuprofen is a non-steroidal anti-inflammatory drugs (NSAID) widely used in pharmaceuticals to treat pain. Pharmaceutical industries have been suffering from solubility issues which affect the delivery efficiency of the drugs. Hence, various methods have been done to enhance the solubility of active pharmaceutical ingredients (API). Cocrystallization has become a novel method in increasing solubility and stability of APIs. This research would like to discuss the cocrystallization study between ibuprofen (pure drug) and glutaric acid (co-former) via slow evaporation technique. Mixing of ibuprofen and glutaric acid with 1:1 molar ratio in propanol solvent were done with five molar ratio starting from 0.5 to 2.5 mole with step size of 0.5. The solutions were then heated until they were fully solubilized and left at temperature room for slow evaporation. Characterization of the cocrystals formed are done using optical microscope (OM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and X-ray powder diffraction (XRD). Based on the OM results, the crystals formed possessed plate shape which is the same with the pure shape of both ibuprofen and glutaric acid. Whereas, the FTIR results showed that cocrystal of IBP:GA was formed due to presence of different bands in comparison with the pure components. The DSC and XRD results analysis were successfully done which reveals that cocrystals of IBP:GA were produced. In conclusion, the IBP:GA cocrystals were successfully formed through slow evaporation technique in propanol solvent.